PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE BAMBOO DANCING DALAM MENINGKATKAN MOTIVASI BELAJAR DI SMP UNISMUH MAKASSAR - Fahril; Subaedah; Bambang Sampurno; Rosmiati; Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study is entitled "The Implementation of the Bamboo Dancing Cooperative Learning Model in Increasing Students' Learning Motivation in Fiqh Subjects in Class VIII B2 of Unismuh Makassar Junior High School." This study aims to determine the implementation of the bamboo dancing cooperative learning model and the increase in students' learning motivation after the model is implemented. This study is a Classroom Action Research (CAR) which was carried out in the 2024/2025 academic year in two cycles, each cycle consisting of two meetings with the stages of planning, implementation, observation, and reflection. The research subjects were 26 students of class VIII B2 of Unismuh Makassar Junior High School. Data collection was carried out through observation to obtain qualitative data and a learning motivation questionnaire to obtain quantitative data. Data were analyzed qualitatively and quantitatively using descriptive statistics in the form of averages and percentages. The results of the study showed an increase in students' learning motivation. In the pre-cycle stage, the average learning motivation was 68.92 with a completeness of 38.42%. In cycle I, it increased to 74.42 with a completion rate of 69.23%, and in cycle II, it increased again to 83.08 with a completion rate of 92.31%. Thus, the implementation of the bamboo dancing cooperative learning model has proven effective in increasing student learning motivation.